(3GdefXheI GdOejGWjIs - (3GdOjQhWj, GdOejGWj, eMeO Hf CMeO, J(B921(3g`s
(3ChdgG (B:s
(3HOCJ HHSe Gddg hGdMeO ChdG (B*** (3Ydi fYe dG JMUi ajeG JfRdG , hHYO UdGI Gddg Ke SdGeg (B*** (3Ydi GdQShd SQ GdhLhO GdecedGs
(3BNQgG (B:s
(3Ydjg UdGI Gddg Ke SdGeg (B***(3hQVhGfg hGdBd eG OeJ HGbjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 336s
(3eYLe GdeDdajf(B: 3 / 64s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs